Possible Association of Nicotinic Acetylcholine Receptor Gene (CHRNA4 and CHRNB2) Polymorphisms with Nicotine Dependence in Japanese Males: An Exploratory Study - Chen, H.-I.; Shinkai, T.; Utsunomiya, K.; Yamada, K.; Sakata, S.; Fukunaka, Y.; Hwang, R.; De Luca, V.; Ohmori, O.; Kennedy, J. L.; Chuang, H.-Y.; Nakamura, J. (Pharmacopsychiatry, 2013)
Smoking is a leading global cause of avoidable mortality. It has been reported that the nicotinic acetylcholine receptor (CHRNA4 and CHRNB2) genes might be associated with smoking behavior in several ethnic populations. However, no study between the 2 genes and nicotine dependence (ND) using a Japanese population has been reported.We examined the association between ND and 5 single nucleotide polymorphisms (SNPs) within the CHRNA4 and 3 SNPs within the CHRNB2 using a well characterized sample of 558 Japanese healthy male workers with a relatively homogeneous background. The Fagerström test for nicotine dependence (FTND) was used to quantify the degree of ND. Additionally, we explored the effect of gene-gene interactions of the 2 genes on ND.We found CHRNB2 rs4845652 genotypes to be associated with FTND scores under an additive genetic model: rs4845652 T-allele carriers had lower ND levels (p=0.038; when adjusted for smoking duration: p=0.052). Furthermore, we demonstrated a possible gene-gene interaction of CHRNA4 and CHRNB2 on ND in a dose-dependent manner: those smokers with CHRNA4 rs1044397 GG or GA genotypes along with CHRNB2 rs4845652 CC genotype are likely to demonstrate higher ND scores.These findings suggest that CHRNB2 rs4845652 T-allele carriers may be associated with lower levels of ND, and that certain allelic combinations of CHRNA4 and CHRNB2 might be correlated with higher ND levels. This preliminary study has certain limitations (issues such as sample size/power and multiple testing) that need to be taken into account, and the present work thus has an experimental nature.
Keywords: nicotine dependence; CHRNA4; CHRNB2; association study; gene-gene interaction; polymorphism